Rojstvo nedonošenega otroka in podpora zdravstvenih delavcev z vidika mater - Černe Kržišnik, Nika (Obzornik zdravstvene nege, 2019)
Introduction: Health care professionals have a considerable impact on how parents experience the birth of a premature infant. The purpose of the study was to research and present findings on the mothers' experience of the birth of a premature infant. Methods: A descriptive phenomenological analysis was carried out. The purposive sample contained eleven mothers who have experienced the premature birth of a child, delivered at between 24 and 35 weeks of gestation. The youngest mother at birth was 24 age old and the oldest mother at birth was 36. For eight mothers premature birth was their first birth experience. The research was conducted between May and June 2017. Data was analysed using the Giorgi approach, which is typically used in phenomenological research. Results: The description has been divided into four main topics that discuss the experience of mothers with preterm childbirth: (1) course of childbirth: wishes and expectations, (2) representation of motherhood: feelings, attachment, empathy, memories, (3) feelings and care for a premature infant in the postpartum period, and (4) (un)professional behaviour of health care staff. Discussion and conclusion: The research has found that most mothers tried to understand the causes for premature birth. Mothers highly valued the support of relatives, health care professionals and other mothers of premature infants. Most mothers experienced negative emotions during childbirth and hospitalisation and an empathic attitude of the staff attitude gave them encouragement, hope and trust.
Keywords: community nurse; health education; home care; hospitalizacija; hospitalization; materinstvo; medosebni odnosi; motherhood; newborn; novorojenec; patronaža; preterm birth; prezgodnji porod; relations; zdravstvena vzgoja